2008
DOI: 10.1021/jf800104x
|View full text |Cite
|
Sign up to set email alerts
|

Ionic Thiocyanate (SCN) Production, Fate, and Phytotoxicity in Soil Amended with Brassicaceae Seed Meals

Abstract: Brassicaceae seed meals produce ionic thiocyanate (SCN (-)), a bioherbicidal compound. This study determined the fate of SCN (-) in a field soil amended with seed meals of Sinapis alba, Brassica juncea, and Brassica napus and quantified crop phytotoxicity by monitoring carrot ( Daucus carota) emergence. Meals were applied at 1 or 2 t ha (-1), and soils were sampled to 35 cm for SCN (-). Maximum SCN (-) (211 micromol kg (-1) of soil) was measured at 5 days in 0-5 cm samples from plots amended with S. alba meal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
42
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(45 citation statements)
references
References 34 publications
3
42
0
Order By: Relevance
“…'Umatilla Russet' was planted in and var. 'Ranger Russet' in 2007and 2008 at a seed piece spacing of 22 cm in rows spaced 86 cm apart. Seed pieces were placed 17 cm deep with a 6-row potato planter.…”
Section: Site Conditions and Managementmentioning
confidence: 99%
See 1 more Smart Citation
“…'Umatilla Russet' was planted in and var. 'Ranger Russet' in 2007and 2008 at a seed piece spacing of 22 cm in rows spaced 86 cm apart. Seed pieces were placed 17 cm deep with a 6-row potato planter.…”
Section: Site Conditions and Managementmentioning
confidence: 99%
“…MSM contains glucosinolates that typically undergo enzymatic hydrolysis to isothiocyanates, SCN2, nitriles, and other compounds when added to moist soil (Brown, Morra, McCaffrey, Auld, & Williams, 1991;Borek & Morra, 2005;Vaughn & Berhow, 2005). The predominant glucosinolate in S. alba seed is 4-hyroxybenzyl glucosinolate or sinalbin, which ultimately yields SCN2, a compound partly responsible for herbicidal activity of MSM (Daxenbichler, Spencer, Carlson, Rose, Brinker, & Powell, 1991;Borek & Morra, 2005;Hansson, Morra, Borek, Snyder, Johnson-Maynard, & Thill, 2008). MSM applied at rates ranging from 113 to 450 g m -2 to the soil surface of container-grown ornamentals reduced annual bluegrass (Poa annua L.), common chickweed [Stellaria media (L.) Vill.…”
Section: Introductionmentioning
confidence: 99%
“…However, in this study, biochar did not alter the fate of glucosinolate or its hydrolysis products in soil (isothiocyanate, thiocyanate, and nitrile) as phytotoxicity produced by rapeseed meal was unmodified by biochar addition. Although decrease of thiocyanate content in soil has been found to be strongly correlated to soil organic matter, it seems that sorption or degradation by abiotic processes only occur at temperatures above 30 • C, whereas microbial degradation prevails below that temperature [14,15].…”
Section: Immediate Phytotoxicity Of Mixtures Of Rapeseed Meal or Ddgsmentioning
confidence: 99%
“…Rapeseed meal has some phytotoxic properties, which are attributed to glucosinolates and their decomposition products [12,13]. As they become non-toxic within days [14,15], rapeseed meal is used on a limited scale as soil amendment for weed or pest suppression [16]. However it has also been suggested as nitrogen fertilizer [17].…”
Section: Introductionmentioning
confidence: 99%
“…Other studies, however, also have reported phytotoxic effects of white mustard seed meal on crops. For example, Hansson et al (2008) reported that the seedling emergence of carrot (Daucus carota L.) was inhibited by white mustard meal soil amendments. Such phytotoxic effects have been attributed to high glucosinolate content in Brassica species and to the gradual release of ionic thiocyanate (SCN − ) from the mustard meal (Borek and Morra 2005;Hansson et al 2008).…”
Section: Introductionmentioning
confidence: 99%